2021
DOI: 10.26434/chemrxiv-2021-01hrg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visible Light-driven Metal-free C–H Functionalization: Access to New Bioactive Tetrahydroisoquinoline-Butenolide Hybrids via Domino Amine Oxidation/Vinylogous Mannich Reaction

Abstract: An efficient metal-free visible light-driven two-step domino reaction towards new bioactive tetrahydroisoquinoline-butenolide hybrid compounds was developed for the first time. Combination of fluorescein as photosensitizer and thiourea as an additive was found to be the most effective way to promote an aerobic amine oxidation/vinylogous Mannich domino reaction sequence with yields up to 97% for a broad substrate scope. While fluorescein without thiourea additive gave product in 84% yield, it was even observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
(22 reference statements)
1
1
0
Order By: Relevance
“…To our delight, we found that all of the tested compounds demonstrated promising anti‐cancer activity, and in the case of compounds 3 aa , 3 ak , 3 an and 3 ea , IC 50 value less than 10 μ M was observed (Figure 2). Importantly, all these four compounds demonstrated anti‐proliferative activity comparable to the reported activity of anti‐cancer drugs Doxorubicin and Etoposide in the A549 cell line [25] . These findings explicitly underline the importance of the developed method, enabling straightforward synthesis of novel S ‐diarylmethane dithiocarbamates that could serve as a promising scaffold for designing effective anti‐cancer drugs.…”
Section: Figuresupporting
confidence: 61%
See 1 more Smart Citation
“…To our delight, we found that all of the tested compounds demonstrated promising anti‐cancer activity, and in the case of compounds 3 aa , 3 ak , 3 an and 3 ea , IC 50 value less than 10 μ M was observed (Figure 2). Importantly, all these four compounds demonstrated anti‐proliferative activity comparable to the reported activity of anti‐cancer drugs Doxorubicin and Etoposide in the A549 cell line [25] . These findings explicitly underline the importance of the developed method, enabling straightforward synthesis of novel S ‐diarylmethane dithiocarbamates that could serve as a promising scaffold for designing effective anti‐cancer drugs.…”
Section: Figuresupporting
confidence: 61%
“…Importantly, all these four compounds demonstrated anti-proliferative activity comparable to the reported activity of anti-cancer drugs Doxorubicin and Etoposide in the A549 cell line. [25] These findings explicitly underline the importance of the developed method, enabling straightforward synthesis of novel Sdiarylmethane dithiocarbamates that could serve as a promising scaffold for designing effective anti-cancer drugs.…”
Section: Communicationsmentioning
confidence: 86%
“…The method included the reaction of tetrahydroisoquinolines 15 a with silyl enol ether of furan 15 b in the presence of organic photocatalyst which is an organic dye (fluorescein), thiourea, and blue LEDs to give lactone-substituted tetrahydroquinoline motifs 15 c in good to excellent yield (Scheme 15). [84] The detailed optimization study revealed that thiourea is essential for the higher yield of the desired 15 c (though without this additive, a maximum 84 % yield could be achieved). The proposed mechanism included a SET between excited fluorescein and amine to generate radical cation intermediate Int-15 d, which was then reacted with molecular oxygen to give The role of thiourea is to scavenge the hydroxy radical, which would most likely interfere in the catalytic cycle.…”
Section: Alkylation Reaction Of α-Amino Radicalsmentioning
confidence: 99%